Phylogeny and systematics of O ld W orld serotine bats (genus E ptesicus , V espertilionidae, C hiroptera): an integrative approach - Javier Juste; Petr Benda; Juan Luis Garcia‐Mudarra; Carlos Ibáñez (Zoologica Scripta, 2013)
Integrative taxonomy aims to document biodiversity by incorporating all useful characters to increase confidence in hypotheses about phylogenetic relationships. In this study, we combine data obtained independently from morphology, two maternally inherited mt DNA genes and two biparentally inherited nu DNA genes to make phylogenetic and taxonomic hypotheses about the Palaearctic members of the bat genus E ptesicus ( V espertilionidae). This genus is distributed worldwide (except for A ntarctica) and is highly diversified, presenting one of the most entangled taxonomic puzzles among all mammals. Our results support restoring the genus R hyneptesicus and separating E . isabellinus and E . pachyomus from E . serotinus and E . ognevi and E . anatolicus from E . bottae . Differences in the phylogenetic hypotheses from mt DNA and nu DNA data suggest the occurrence within E . serotinus of evolutionary processes such as mt DNA capture and secondary contacts between partially differentiated ecomorphs. These two evolutionary processes deserve more in‐depth studies within the group.